Dietary supplementation with honeycomb extracts positively improved egg nutritional and flavor quality, serum antioxidant and immune functions of laying ducks - Chen, Xiaolian; Xiong, Pingwen; Song, Wenjing; Song, Qiongli; Zou, Zhiheng; Huang, Jiangnan; Chen, Jiang; Xu, Chuanhui; Su, Weide; Ai, Gaoxiang; Wei, Qipeng (Frontiers in Veterinary Science, 2023)
This study aims to evaluate the effects of honeycomb extracts on the laying performance, egg nutritional and flavor quality, serum biochemical indexes, and antioxidant and immune status in laying ducks. A total of 672 Shanma laying ducks, 28 weeks of age, were randomly distributed into four dietary treatments with 6 replicates of 28 birds. The birds in each treatment were fed the basal diet supplemented with 0 (control group), 0.5, 1.0 or 1.5 g/kg honeycomb extracts, respectively. Feed and water were provided ad libitum for 45 days. The results showed that honeycomb extract addition significantly increased the average daily feed intake but did not affect the other laying performance indexes, egg quality or serum biochemical indexes of laying ducks. Dietary supplementation with honeycomb extracts significantly increased crude protein content and decreased the contents of cholesterol and trimethylamine in eggs. Diets supplemented with 1.5 g/kg honeycomb extracts significantly improved egg total amino acids and flavor amino acids contents, monounsaturated fatty acids and polyunsaturated fatty acids composition and enhanced the serum antioxidant activity and immune functions of ducks. It was concluded that dietary supplementation with honeycomb extracts positively reduced the contents of egg cholesterol and trimethylamine, improve egg amino acids contents and fatty acid profiles, enhanced serum antioxidant and immune status of laying ducks. The recommended supplemental level of honeycomb extracts was 1.5 g/kg in the diet of laying ducks.